Cost Observation in Natural Monopoly Settings: The Relevance of Jean-Jacques Laffont and Jean Tirole's Thoughts in The Regulation of Natural Monopoly Companies - Jerry Marmen; Airlangga Surya Kusuma (International Journal of Economics Development Research (IJEDR), 2023)
Government intervention is necessary to protect consumer interests and prevent companies in monopoly markets from exploiting consumers by setting high prices. Regulations such as business competition laws and price regulations can be implemented to prevent monopoly markets from exploiting consumers. However, implementing price regulation in natural monopolies is challenging due to challenges such as determining accurate marginal costs, monitoring and enforcing regulations, and ensuring compliance by monopolists. Thus, effective regulation must be holistic, covering aspects of price, service quality, and innovation incentives, and supported by strong transparency and accountability mechanisms to ensure compliance and protect overall consumer interests. The study concludes that there is a need for regulation in monopoly markets, particularly in sectors like water utilities, electricity, and rail transportation where high fixed costs and large economies of scale make one firm more efficient than several competing firms. The government plays a crucial role in implementing regulations to protect consumers and ensure market efficiency. Further research is needed to test the effectiveness of incentive and fine mechanisms in other sectors, develop econometric models to measure monopoly efficiency and conduct international policy evaluations. By combining theoretical and empirical approaches, the proposed policies can improve efficiency, consumer welfare, fiscal sustainability, and better management of public resources.